Effect of CFRP Confinement on AAR-Induced Expansion of Concrete Columns - KUBAT, THAMER; AL-MAHAIDI, RIADH; SHAYAN, AHMAD (Journal of Duhok University, 2017)
The effect of the alkali-aggregate reaction (AAR) in concrete, which has an adverse effect on its durability.  In order to extend concrete’service life-span it is necessary to find a novel material to reduce or limit AAR-induced expansion and improve the strength capacity of the affected concrete. Carbon fibre reinforced polymers (CFRPs) are one of several materials used to rehabilitate affected concrete members. Twenty circular concrete columns 200 mm in diameter and 500 mm in height were cast from reactive (AAR) concrete. During six months of storage at 38º C and 98% relative humidity, several ages of 15, 30, 45, 60, 90 and 120 days after casting to represent different levels of expansion during AAR development were selected to confine the affected columns using CFRP composites. Strain behaviour in concrete and steel were monitored, before and after confinement, for different wrapping times.  The results indicate the efficiency of using CFRP to reduce the rate of expansion in both steel and concrete. The results show also show that the efficiency of reducing AAR-induced expansion depends on the time of wrapping and the number of CFRP layers applied to the affected columns